2023
DOI: 10.1002/ajmg.a.63368
|View full text |Cite
|
Sign up to set email alerts
|

Α rare case of myopathy, lactic acidosis, and severe rhabdomyolysis, due to a homozygous mutation of the ferredoxin‐2 (FDX2) gene

Abstract: Mitochondrial myopathy is a severe metabolic myopathy related to nuclear or mitochondrial DNA dysfunction. We present a rare case of mitochondrial myopathy, presented with multiple episodes of proximal muscle weakness, lactic acidosis, and severe rhabdomyolysis (CPK 319,990 U/L, lactic acid 22.31 mmol/L, and GFR 3.82 mL/min/1.73m2). She was hospitalized in the pediatric intensive care unit due to acute kidney injury, elevated blood pressure, and deterioration of respiratory and cardiac function. Investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Previous study showed that patient with FDX2 ‐related disorder is sensitive to high dextrose fluid, leading to increased lactate production. 10 , 11 The proband also demonstrated increased blood lactate with the increase of glucose infusion rate. This phenomenon has been known in PDH deficiency, and in fact, the patients with PDH deficiency responded to ketogenic diet.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous study showed that patient with FDX2 ‐related disorder is sensitive to high dextrose fluid, leading to increased lactate production. 10 , 11 The proband also demonstrated increased blood lactate with the increase of glucose infusion rate. This phenomenon has been known in PDH deficiency, and in fact, the patients with PDH deficiency responded to ketogenic diet.…”
Section: Discussionmentioning
confidence: 92%
“… 9 The previously reported patients with predominant muscular presentation harbor the variants affecting the initiator codon. 6 , 7 , 8 , 10 , 11 The proband is the first reported patient with compound heterozygous variants. The patients harboring missense variants affecting initiator codon did not demonstrate extramuscular involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations